An Analysis upon Nationalism in the Writing of Rabindranath Tagore and W. B. Yeats: Exploring Nationalism and its Evolution in the Writings of Tagore and Yeats (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Nationalism is a complex term, torsade with the forces of colonial and postcolonial witness. It is a quite difficult idea to be explained, as today every nation bears the sense of nationalism but not everyone is getting the same right and space. Time to time the idea emerge with many new additions and develop the base of the concept. Rabindranath is the emblem of Bengali nation but still regarded as an anti-nationalist. Who always stands for his own people but there is no abrogation for people belong to any other country, religion and nation. Again, Yeats is representing both Ireland and England. In the late nineties there was a radical change all over the world. The powerful countries became one another’s rival. Colonial rulers were threatened by the rise of the revolutionary nationalist. The whole world came to a tumultuous situation. Both Rabindranath and Yeats concentrated on that part of the human history. Their nationalist perception turned into a new direction. It is because of the aggressive nationalistic view of that time.